Sovereign Wealth Fund: A Bibliometric Review - Mujahidah , Anisa Syahidah (Business and Sustainability, 2023)
This bibliometric study maps out research related to the development of Sovereign Wealth Fund research trends published by leading journals from 2007 to 2022 that have been indexed by Scopus. The analysis is focused on keyword trends, authors and institutions. The data analyzed were 734 research publications. The search term was 'Sovereign Wealth Fund'. Descriptive statistical methods were used, and bibliometric analysis was performed using the VOSViewer application to determine the bibliometric map. The number of articles discussing the theme of the Sovereign Wealth Fund shows an increasing trend from year to year. The most popular keyword used is Sovereign Wealth Fund. The most prolific writer was Dixon A.D. Meanwhile, the country with the most popular authors and the most is the United States. The research provides information for researchers who focus on research in the Sovereign Wealth Fund field. In the end, this theme has the potential to continue to be developed.